METHODS AND NARRATIVE STYLE OF VALENTIN PIKUL - Elena Shevchenko, (Educational Research in Universal Sciences, 2023)
The article gives a brief overview of Pikul’s works, his style, methods of describing events, historical figures and just people of the past time, shows the attitude of historians and critics of novels and stories of the writer.